“Round Peg in a Square Hole”: Lessons from Community Health Promotion Practice on Dynamics of Accountability, Reporting and Evaluation, and Governance - Julia Fursova; Gillian Kranias (Journal of Public and Nonprofit Affairs)
This paper presents results from a small-scale institutional ethnography study of reporting requirements and evaluation practices in two urban community health centers (CHCs), as a sample of community-based nonprofit organizations that focus on social justice and health equity. The study illuminated complex relationships among accountability, reporting and evaluation, and governance. Among the CHCs, reporting and evaluation practices consistent with goals of obtaining social justice and health equity were undermined by an imbalance toward funder-oriented functional accountability. Analysis of accountability and reporting practices as systemic factors shaping knowledge production, decision-making, and action revealed notable consequences for CHCs’ health promotion practice. This paper proposes a wholistic accountability model to encourage equitable power relations in evaluation, enable participatory methods, and better align CHC knowledge production and governance systems with their health promotion goals. This study further adds to the growing literature supporting critical attention to nonprofit accountability in the context of systems change work.